Encapsulation of urea and caffeine in Cu3(BTC)2 metal–organic framework. Issue 2 (17th February 2016) - Loera-Serna, Sandra; Zarate-Rubio, Jocelyn; Medina-Velazquez, Dulce Y.; Zhang, Lei; Ortiz, Elba
Abstract : The Cu3 (BTC)2 metal–organic framework (MOF) (BTC = 1, 3, 5-benzenetricarboxylate), also known as HKUST-1 (or MOF-199), is one of the most studied MOFs because it has a large surface area, high pore volume, high chemical stability and the ability to bind water, among other molecules, by coordinating to the unsaturated Cu(II) sites. In this study, Cu3 (BTC)2 was used for the first time to remove the pharmaceutical products of urea and caffeine. Two strategies for retention of urea and caffeine in Cu3 (BTC)2 were studied. The first strategy corresponds to in situ encapsulation, where urea and caffeine were added to Cu3 (BTC)2 synthesis precursors and the porous structure was formed around the urea or caffeine molecules resulting in the encapsulation. The second one corresponds to post-synthesis encapsulation. The adsorption of urea or caffeine in MOF structure was realized by adding the as-synthesized dry Cu3 (BTC)2 into urea or caffeine aqueous solution. The results show that in situ encapsulation of caffeine and urea in Cu3 (BTC)2 produced a guest loading of 38 and 25 wt%, respectively, whereas, post-synthesis encapsulation had a guest loading of 52 and 30 wt% for caffeine and urea, respectively.